1981
DOI: 10.1002/pol.1981.180190406
|View full text |Cite
|
Sign up to set email alerts
|

Model networks of end‐linked polydimethylsiloxane chains. XI. Use of very short network chains to improve ultimate properties

Abstract: Elastomeric networks were prepared by tetrafunctionally end‐linking mixtures of various proportions of relatively long and very short polydimethylsiloxane (PDMS) chains. The former had a number‐average molecular weight of 18,500 and the latter either 660 or 220 g mole−1. The series of (unfilled) bimodal networks thus prepared were studied in elongation to the rupture point at 25°C, and in swelling equilibrium in benzene at room temperature. Elasticity constants characterizing the Gaussian regions of the stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
69
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(78 citation statements)
references
References 27 publications
9
69
0
Order By: Relevance
“…For instance Yanyo observed that in polydimethyl siloxane networks, the fracture behaviour depends also on the length distribution of EACs [9]. This was confirmed by Mark and co-workers [1,2] who studied a series of polydimethyl siloxane networks based on long chains to which variable quantities of short chains were added. It appeared that the modulus increases regularly with the average crosslink density.…”
Section: Introductionmentioning
confidence: 72%
See 3 more Smart Citations
“…For instance Yanyo observed that in polydimethyl siloxane networks, the fracture behaviour depends also on the length distribution of EACs [9]. This was confirmed by Mark and co-workers [1,2] who studied a series of polydimethyl siloxane networks based on long chains to which variable quantities of short chains were added. It appeared that the modulus increases regularly with the average crosslink density.…”
Section: Introductionmentioning
confidence: 72%
“…However, the plot displays a positive curvature which could be linked to a specificity of the crosslinking process and can be explained as follows: random crosslinking creates a new population of chains shorter than initial ones. It is interesting to compare this trend with the one of model networks having a bimodal distribution of chain lengths [1,2] (Fig. 9a).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…[18][19][20][21][22][23][24] In particular, Mark et al [19][20][21][22][23] prepared the model rubbers having a known, bimodal distribution of the strand length (through end-linking of bimodal prepolymers) to examine the relationship between this distribution and modulus/deformation of the rubbers. However, their model rubbers…”
mentioning
confidence: 99%